Tocosome: A Cutting-Edge Drug Delivery Platform Combining Phospholipids and Tocopheryl Phosphates - Sivaram R; H. Gayathri; N. Damodaran (The Bioscan, 2025)
The development of novel nanocarrier systems for drug delivery is crucial for enhancing therapeutic efficacy and stability while minimizing toxicity. In this study, we explore the potential of α-tocopheryl phosphate (TP) and di-α-tocopheryl phosphate (T2P), two derivatives of vitamin E, as key components in tocosome-based drug delivery systems. Tocosomes were formulated using the Mozafari method, incorporating TP, T2P, and various lipids/phospholipids, including phosphatidylcholine, stearyl amine, Phospholipon 90H, and Phospholipon 100H, with and without cholesterol. This solvent-free preparation technique avoids the use of potentially toxic solvents, detergents, and mechanical stressors such as sonication or high-shear force homogenization. The formulated tocosomes demonstrated a narrow size distribution, high encapsulation efficiency, and excellent long-term stability, retaining their integrity for over two years. Using 5-fluorouracil as a model drug, we confirmed the feasibility of these nanocarriers for drug delivery applications. These findings highlight the potential of TP- and T2P-based tocosomes as a biocompatible, stable, and efficient drug delivery platform, offering promising applications in pharmaceutical and biomedical fields.